2000
DOI: 10.1006/mthe.2000.0124
|View full text |Cite
|
Sign up to set email alerts
|

Theory and in Vivo Application of Electroporative Gene Delivery

Abstract: Efficient and safe methods for delivering exogenous genetic material into tissues must be developed before the clinical potential of gene therapy will be realized. Recently, in vivo electroporation has emerged as a leading technology for developing nonviral gene therapies and nucleic acid vaccines (NAV). Electroporation (EP) involves the application of pulsed electric fields to cells to enhance cell permeability, resulting in exogenous polynucleotide transit across the cytoplasmic membrane. Similar pulsed elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
166
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(172 citation statements)
references
References 75 publications
3
166
0
3
Order By: Relevance
“…It was already proposed that this observation could be due to the specific properties of the tumor tissue, such as differences in tissue organisation, in extracellular matrix, presence or absence of necrosis, overall tissue conductivity, the ability of cells to express transfected genes, cell density, and cell size. 13,19,33 A correlation between cell density and transfection efficiency by electroporation demonstrated that lower cell density yielded better transfection (Fig 7 ), which is in agreement with in vitro data obtained on adherent cells. 36 The correlation was not very high, as only four tumor types were included and should be expanded in a further study to prove the hypothesis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was already proposed that this observation could be due to the specific properties of the tumor tissue, such as differences in tissue organisation, in extracellular matrix, presence or absence of necrosis, overall tissue conductivity, the ability of cells to express transfected genes, cell density, and cell size. 13,19,33 A correlation between cell density and transfection efficiency by electroporation demonstrated that lower cell density yielded better transfection (Fig 7 ), which is in agreement with in vitro data obtained on adherent cells. 36 The correlation was not very high, as only four tumor types were included and should be expanded in a further study to prove the hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…13 In the case of tumors, many different electrical parameters for electroporation were employed for delivering plasmid DNA encoding either reporter (luciferase, -galactosidase, GFP ) or therapeutic genes (IL -12, Stat3, GM -CSF, IL -2). 25 -35 Our study focused on optimisation of plasmid DNA delivery to tumors by using different electrical parameters and DNA concentrations in the SaF tumor model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, efficacy is also dependent on the concentration gradient of the molecules that are to be delivered. 21 The longer the loading period, the longer the cell surface is open. Hence, it is likely that more of the agent would be transferred from the extracellular to the intracellular space.…”
Section: Low-voltage Ep and Antiangiogenic Gene Therapy M Uesato Et Almentioning
confidence: 99%
“…Then a sequential process progresses spontaneously with escape from endosomes, dissociation of complexes, and diffusion of naked DNAs in the cytoplasm to reach the nucleus [4][5][6]. On the other hand, physical approaches such as microinjection [7,8] and electroporation [9] are performed to incorporate naked DNAs directly into cytoplasm across the plasma membrane. Some naked DNAs diffuse in the cytoplasm to the nucleus [10].…”
Section: Introductionmentioning
confidence: 99%